Preparing teachers in grades K-6 to help young pupils learn physics: toward a common research agenda. Issue 1 (May 2021) - Vokos, S; Corni, F; Vidic, E; Maurizio, R; Michelini, M; Kapanadze, M; López-Gay, R; Martínez-Chico, M; Jiménez-Liso, M R; Castillo, F J; Spyrtou, A; Chaitidou, M; et al.
Abstract: Standards documents envision that students in grades K-6 engage in developmentally appropriate yet substantive learning in physics and physical science. Students are expected to engage in the practices of the discipline, trying to develop – and experimentally defend – their own explanations of rich everyday phenomena. Teachers need special preparation to meet this challenge. Traditional preparation in lecture-based science university courses or courses that emphasize engaging demonstrations with little intellectual ballast are unlikely to yield the kind of rich experiential and rich discourse-based instructional environment for young pupils to thrive. In this GIREP Symposium, speakers introduced promising models for teacher preparation and enhancement and contribute to a discussion in search of a coherent research-based agenda for like-minded GIREP members.